Design Common Mode Logic(CML) Frequency Divider in CMOS Porcess Technology - Mastura Binti Omar, Mastura (Universiti Teknologi Petronas, 2009)
The objective of this project is to design current mode logic (CML) frequency divider in CMOS technology. The current spikes that occur during transition between tacking and latch mode in transistor will degrade the performance of the frequency divider. The parasitic capacitances that exist in two transistor of tracking circuit directly contribute to the latch delay. The fundamental of this project is to understand the basic operation of CML of D Flip-flop based frequency divider. The new circuit which known as modified frequency divider is designed in order to overcome the current spike that occur during the transition between track and latch mode hence to reduce the rise time and fall time at the output. The modified frequency divider is able to reduce 20% up until 57.14% of the current spike that occurs during the transition between the track and latch mode. It also managed to reduce 11.76% up until 53.85% of the rise time and fall time at the output voltage hence reduce the latch delay.